The Grammar of Customary Law - Webber, Jeremy (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractAll law is customary. This article explores how we should conceive of the customary nature of law, proposing a framework for understanding how legal orders are related to their various societies. The article builds upon the pragmatist conception of law developed by Lon Fuller and Gerald Postema, but it goes well beyond their accounts, arguing that their predominantly functionalist approaches are inadequate. Although law does serve to coordinate social interaction, it does so through specific conceptual languages, through particular grammars of customary law. Law can only be understood if one takes those grammars seriously.The article pursues this argument by drawing comparisons between indigenous and non-indigenous legal orders, both to expand the comparative range and to explore what indigenous legal orders can reveal about law generally. It explores the limitations of functionalist accounts (including law and economics) in the law of persons and property, in presumptions about the foundational requirements of legal order, and in the presence of the sacred or mythic in law. The article concludes that attending to the various grammars of customary law allows one to engage, productively and with insight, in legal reasoning across the normative divide separating different legal cultures.